The Use of Web Technologies in the Organization of Independent Work of Students - Eshmuradov Azamat Guzorovich (Genius Publishing Group, 2023)
The use of web technologies to improve the efficiency of knowledge and skills of students for independent work in the higher education system, as well as the provision of independent work using the interactive services of the google search engine as a topshriq and their online assessment, is an important factor in the formation of creative rotation skills in the student. Therefore, this article describes the effective use of web technologies and its interactive services
Keywords: Credit-module; Web page; web technology; Google Docs